Efficiency of Bio-Extracts on Bacterial Fruit Blotch of Watermelon Varieties as Affected by Climatic Changes, Growth, and Yield Parameters at Ardo Kola in 2020 and 2021 - O, Aji P.; A, Tunwari B.; Y, Madinatu; R, Umaru; O, Olawuyi P.; Y, Yunusa A. (Kwaghe International Journal of Sciences and Technology, 2025)
Bacterial fruit blotch (BFB), caused by Acidovorax citrulli, is a highly destructive disease that significantly reduces watermelon yield and quality under favorable environmental conditions. This study assessed the effectiveness of selected bio-extracts (Neem oil, Garlic oil, Jatropha oil, and their combinations) and varietal responses in managing BFB incidence, growth performance, and yield of watermelon in Ardo Kola, Taraba State, during the 2020 and 2021 cropping seasons. Field trials were conducted using a randomized complete block design with three replications. Data were collected on disease incidence, number of leaves, and fruit yield. Results showed that Neem oil and Streptomycin treatments significantly reduced BFB incidence compared to the untreated control. Among the tested varieties, Kaolack consistently recorded the highest yield, outperforming Local and Sweet Sangariax varieties. Year-to-year climatic variations influenced both disease severity and yield outcomes; notably, 2021 experienced lower disease incidence and higher yields due to more favorable rainfall distribution and lower humidity. The study concludes that integrating bio-extract applications with strategic varietal selection offers an eco-friendly and effective approach for managing BFB in watermelon production, particularly under variable climatic conditions.